(untitled) (Brazilian Journal of Pharmaceutical Sciences, 2022)
Fluoroquinolones are an important class of antimicrobial agents to manage infectious diseases. However, knowledge about how host bile acids are modified by fluoroquinolones is limited. We investigated and compared the impact of fluoroquinolones on circulating bile acid profiles and gut microbiota from in vivo studies. We administered ciprofloxacin (100 mg/kg/day) or moxifloxacin (40 mg/kg/day) orally to male Wistar rats for seven days. Fifteen bile acids (BAs) from the serum and large intestine were quantified by HPLC-MS/MS. The diversity of gut microbiota after ciprofloxacin and moxifloxacin treatment was analyzed using high-throughput, next-generation sequencing technology. The two fluoroquinolone-treated groups had different BA profiles. Ciprofloxacin significantly reduced the hydrophobicity index of the BA pool, reduced secondary BAs, and increased taurine-conjugated primary BAs in both the serum and large intestine as compared with moxifloxacin. Besides, ciprofloxacin treatment altered intestinal microbiota with a remarkable increase in Firmicutes to Bacteroidetes ratio, while moxifloxacin exerted no effect. What we found suggests that different fluoroquinolones have a distinct effect on the host BAs metabolism and intestinal bacteria, and therefore provide guidance on the selection of fluoroquinolones to treat infectious diseases.